2014
DOI: 10.1590/s1679-78252014000500007
|View full text |Cite
|
Sign up to set email alerts
|

Application of nonlocal elasticity and DQM to dynamic analysis of curved nanobeams

Abstract: In this paper, a new numerical technique, the differential quadrature method (DQM) has been developed for dynamic analysis of the nanobeams in the polar coordinate system. DQ approximation of the required partial derivatives is given by a weighted linear sum of the function values at all grid points. A semicircular arch with small-scale effects is investigated by the nonlocal continuum theory with simply supported boundary conditions. The governing equations for Euler-Bernoulli nonlocal beam models are derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…In Eftekhari and Jafari (2012c) the capability of the DQM for handling the time-dependent Dirac-delta function was discussed at length and it was concluded that there are some major limitations in the choice of time steps and mesh sizes. Most recently, Nikkhoo et al (2012), Nikkhoo and Kananipour (2014) also Kananipour et al (2014) have proposed a formulation based on the DQM for transient dynamic analysis of curved beams traversed by moving concentrated loads. But, no details were given how the time-dependent Diracdelta function was approximated or treated numerically in their study.…”
Section: Introductionmentioning
confidence: 99%
“…In Eftekhari and Jafari (2012c) the capability of the DQM for handling the time-dependent Dirac-delta function was discussed at length and it was concluded that there are some major limitations in the choice of time steps and mesh sizes. Most recently, Nikkhoo et al (2012), Nikkhoo and Kananipour (2014) also Kananipour et al (2014) have proposed a formulation based on the DQM for transient dynamic analysis of curved beams traversed by moving concentrated loads. But, no details were given how the time-dependent Diracdelta function was approximated or treated numerically in their study.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure for solving equations (49) and (50) is similar to that described in the previous section. We assume that an equal number of grid points to be used for approximation of functions W(x, t) and '(x, t).…”
Section: (04x4l)mentioning
confidence: 99%
“…We assume that an equal number of grid points to be used for approximation of functions W(x, t) and '(x, t). By applying the DQ-IQ coupled approach, equations (49) and (50) are reduced to the following system of ODEs in time…”
Section: (04x4l)mentioning
confidence: 99%
“…However, Yan and Jiang [29] have investigated the electromechanical response of a curved piezoelectric nanobeam with the consideration of surface effects. In addition, a new numerical technique, the differential quadrature method, has been developed for dynamic analysis of the nanobeams in the polar coordinate system by Kananipour et al [30]. Moreover, Khater et al [31] have investigated the effect of surface energy and thermal loading on the static stability of nanowires.…”
Section: Introductionmentioning
confidence: 99%